International survey for assessing COVID-19’s impact on fear and health: study protocol - Lok, Kris Yuet-Wan; Daniel Yee Tak, Fong; Janet Y.H., Wong; Mandy, Ho; Edmond PH, Choi; Vinciya, Pandian; Patricia M, Davidson; Wenjie, Duan; Marie, Tarrant; Jung Jae, Lee; Chia-Chin, Lin; Che Hasan, Muhammad Kamil; et al. (BMJ Publishing Group, 2021)
Introduction COVID-19, caused by the SARS-CoV-2, has been one of the most highly contagious and rapidly spreading virus outbreak. The pandemic not only has catastrophic impacts on physical health and economy around the world, but also the psychological well-being of individuals, communities and society. The psychological and social impacts of the COVID-19 pandemic internationally have not been well described. There is a lack of international study assessing health-related impacts of the COVID-19 pandemic, especially on the degree to which individuals are fearful of the pandemic. Therefore, this study aims to (1) assess the health-related impact of the COVID-19 pandemic in community-dwelling individuals around the world; (2) determine the extent various communities are fearful of COVID-19 and (3) identify perceived needs of the population to prepare for potential future pandemics.